Phenanthrene Dimers: Promising Source of Biologically Active Molecules - De Natale, Antonino; Pollio, Antonino; De Marco, Anna; Luongo, Giovanni; Di Fabio, Giovanni; Zarrelli, Armando (Current Topics in Medicinal Chemistry, 2022)
To date, just over a hundred phenanthrenoid dimers have been isolated. Of these, forty-two are completely phenanthrenic in nature. They are isolated from fourteen genera of different plants belonging to only five families, of which Orchidaceae is the most abundant source. Other nine completely acetylated and five methylated dimers were also defined, which were effective in establishing the position of the free hydroxyls of the corresponding natural products, from which they were obtained by semi-synthesis. Structurally, they could be useful chemotaxonomic markers considering that some substituents are typical of a single-family, such as the vinyl group for Juncaceae. From a biogenetic point of view, it is thought that these compounds derive from the radical coupling of the corresponding phenanthrenes or by dehydrogenation of the dihydrophenanthrenoid analogs. Phenanthrenes or dihydroderivatives possess different biological activities, e.g., antiproliferative, antimicrobial, antiinflammatory, antioxidant, spasmolytic, anxiolytic, and antialgal effects. The aim of this review is to summarize the occurrence of phenanthrene dimers in the different natural sources and give a comprehensive overview of their structural characteristics and biological activities.
Keywords: Biphenanthrene derivatives